Pengaruh Persepsi Manfaat, Persepsi Kemudahan, Persepsi Keamanan, dan Ketersediaan Fitur terhadap Minat Penggunaan Aplikasi BRImo (Studi Kasus pada Mahasiswa FEB Unisma Angkatan 2019) - Amira Fajril Lutfiah; Ronny Malavia Mardani; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Mobile banking is an application developed by banks to serve customers 24 hours a day. BRImo is a mobile banking application created by a bank from Indonesia. This study aims to determine the effect of perceived usefulness, perceived ease of use, perceived security, and feature availability on interest in using the BRImo application. explanatory research with a quantitative approach is used as the type of this research. 90 FEB UNISMA students class of 2019 is used as sample. Methods of the data collection using a questionnaire. While the method of data analysis using instrument tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The results of the study showed that perceived usefulness, perceived ease of use, and perceived security have a significant effect on interest in using the BRImo application. Meanwhile, feature availability has no effect and is not significant on interest in using the BRImo application. Keywords: Perceived usefulness, Perceived ease of use, Perceived of security, and Availability of features